2014
DOI: 10.1186/1756-0500-7-622
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of non tuberculous mycobacteria from humans and animals in Namwala District of Zambia

Abstract: BackgroundThe genus Mycobacterium contains more than 100 species, most of which are classified as non-tuberculous mycobacteria (NTM). In Zambia, the NTM are slowly becoming recognized as pathogens of major public health significance with the advent of Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS). This study aimed at reporting the isolated NTM and ascertains their zoonotic potential and diagnostic significance in Zambia.MethodA total of 100 sputum samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The NTM species such as M. fortuitum and M. gordonae are so ubiquitous that they have previously been recovered from cattle in Ethiopia [7, 29], and human, animals and the environment elsewhere in Africa [28, 3032]. Mycobacterium peregrinum, which is a rapidly growing, ubiquitous and an opportunistic but potentially pathogenic NTM [33] was isolated more frequently in this study.…”
Section: Discussionmentioning
confidence: 66%
“…The NTM species such as M. fortuitum and M. gordonae are so ubiquitous that they have previously been recovered from cattle in Ethiopia [7, 29], and human, animals and the environment elsewhere in Africa [28, 3032]. Mycobacterium peregrinum, which is a rapidly growing, ubiquitous and an opportunistic but potentially pathogenic NTM [33] was isolated more frequently in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Organisms act in synergy, potentiating the colonization by other bacteria. Although mixed infection with NTM has been reported, attention should be given to NTM in the future as several studies have recognized the significance of NTM as a major public health issue around the world (Moore et al., ; Kankya et al., ; Kim et al., ; Malama et al., ; Temmerman et al., ). Furthermore, NTM has been found to interfere with the diagnosis of TB in cattle; indeed, some cross reactions between the antigens of NTM with those used for diagnostic purposes such as M. avium and M. fortuitum may compromise the diagnosis and control of bovine tuberculosis (De la Rua‐Domenech et al., ; Gcebe et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Mycobacterium contains more than 170 species (http://www.bacterio.net/mycobacterium.html), most of which are classified as NTM or potentially pathogenic mycobacteria (PPM; Chege et al., ; Kim et al., ; Malama et al., ; Tortoli, ) and mycobacteria belonging to the Mycobacterium tuberculosis complex (MTC). MTC comprises M. tuberculosis , M. bovis , M. africanum , M. canetti , M. pinnipedii , M. caprae , M. microti , M. mungi , Dassie bacillus , Oryx bacillus and the attenuated M. bovis bacille Calmette–Guerin (BCG) vaccine strain.…”
Section: Introductionmentioning
confidence: 99%
“…The novel NTM species Mycobacterium chimaera was isolated and characterized in Italy in 2004 (Tortoli et al 2004), and additional cases of infection with this species were reported in Germany in 2008 and in the United States in (Bills et al 2009Schweickert et al 2008). More recently this species was isolated and identified in Namwala District of Zambia in 2014 (Malama et al 2014). Moreover, Boyle et al reported that M. chimaera was isolated more often than M. intracellulare in Chicago, United States (Boyle et al 2015).…”
Section: Introductionmentioning
confidence: 96%